2005
DOI: 10.1111/j.1540-8175.2005.04051.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Echocardiography in Assessing the Mechanism and Effect of Ramipril on Functional Mitral Regurgitation in Dilated Cardiomyopathy

Abstract: The objectives of this article are to determine the possible mechanism of functional mitral regurgitation in patients with dilated cardiomyopathy (DCM) and to know the effect of ramipril on left ventricle (LV) and mitral regurgitation by ECHO. Several postulates are put forth for functional mitral regurgitation in DCM, and mitral annular dilatation is said to be the primary mechanism in the past, but the exact mechanism is not clear. Though angiotensin converting enzyme (ACE) inhibitors are known to remodel th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…Alterations of the geometric shape of the left and right ventricles have been reported in adult and pediatric patients as markers of cardiac dysfunction in which the ventricle appears to be flattened or rounded, depending on the underlying abnormality . One method used for evaluation of ventricular shape involves measuring the end‐diastolic BAL and TL for the right and left ventricular chambers and computing the GSI using either BAL/TL or TL/BAL (Figure ) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations of the geometric shape of the left and right ventricles have been reported in adult and pediatric patients as markers of cardiac dysfunction in which the ventricle appears to be flattened or rounded, depending on the underlying abnormality . One method used for evaluation of ventricular shape involves measuring the end‐diastolic BAL and TL for the right and left ventricular chambers and computing the GSI using either BAL/TL or TL/BAL (Figure ) …”
Section: Discussionmentioning
confidence: 99%
“…Alterations of the geometric shape of the left and right ventricles have been reported in adult and pediatric patients as markers of cardiac dysfunction in which the ventricle appears to be flattened or rounded, depending on the underlying abnormality. [21][22][23][24][25][26][27][28][29][30][31][32][33][34] One method used for evaluation of ventricular shape involves measuring the end-diastolic BAL and TL for the right and left ventricular chambers and computing the GSI using either BAL/TL or TL/BAL (Figure 4). 8,21,35 Once an abnormal GSI was identified, the only group that showed a significant increase in the TL, thus leading to a more globular-shaped heart, was the group of fetuses with cardiac dysfunction (Table 5), which was similar in fetuses with an estimated fetal weight below the 10th centile (27.7%) and above the 10th centile (29.5%).…”
Section: Discussionmentioning
confidence: 99%
“…The sphericity index (SI) is used to evaluate the shape of the right and left ventricles of the heart and is derived by calculating the ratio between the end-diastolic mid-basal-apical and transverse lengths (Figure 1a). SI has been examined in adult and pediatric patients and found to be a useful tool to detect abnormal cardiac function resulting from remodeling of the ventricular chamber [1][2][3][4][5][6][7][8][9][10][11][12][13] . Only six studies have evaluated the SI of the fetal heart [14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the cardiac renin-angiotensin-aldosterone system (RAAS) is up-regulated in experimentally induced MR. 21 Pharmacologic blockade of the RAAS with ACE-inhibitors in patients with moderate and severe MR results in clinical benefits, improvement in LV performance, and echocardiographic parameters. 8,11,22,23 The data showed that single-dose enalapril treatment for paediatric patients reduces the severity of MR and improves the LV loading conditions and systolic performance without impairment of myocardial contractility.…”
Section: Discussionmentioning
confidence: 99%